Advanced Approach for Estimating Failure Rate Using Saddlepoint Approximation - Alya Al Mutairi (MDPI AG, 2021)
In the present study paper, a failure (hazard) rate function approximates the probability distribution for the linear combination of a random variable considered a highly complex model. The saddlepoint approximation approach is used to approximate the probability mass function and the cumulative distribution function to derive the approximation of the failure (hazard) rate with a high level of accuracy. The superior performance of this method is shown by numerical simulations and comparison with the performance of other approximation methods.